Hard coating film and method for producing the same, and display device

By using a hard coat composition with negative curing shrinkage on the transparent resin film, the film warping problem caused by the increase in the thickness of the hard coat layer is solved, and the curling inhibition and the stability of the hard coat film are improved.

CN115175810BActive Publication Date: 2025-04-15KANEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180016790.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-25
Filing Date
2021-02-19
Publication Date
2025-04-15
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

The prior art increases the thickness of the hard coating layer, which easily leads to warping of the transparent resin film, which in turn affects the processing and application of the film.

Method used

By using a hard coat composition with a negative curing shrinkage, the thickness of the hard coat layer and the difference in linear expansion of the transparent resin film are controlled to reduce the curling phenomenon.

Benefits of technology

Even if the hard coat layer is thick, curling can be suppressed, improving the stability and application performance of the hard coat film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115175810B_ABST
    Figure CN115175810B_ABST
Patent Text Reader

Abstract

The hard coating film (10) has a hard coating layer (3) formed of a cured product of a hard coating composition on one surface of a transparent resin film (1). The thickness of the hard coating layer is at least 0.15 times the thickness of the transparent resin film. The hard coating composition has a negative curing shrinkage. The absolute value of the curling amount measured by cutting the hard coating film into a square of 100 mm × 100 mm is preferably less than 20 mm. The hard coating layer may include a cured product of a polyorganosiloxane compound having an alicyclic epoxy group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hard coating film having a hard coating layer on a main surface of a transparent resin film and a method for producing the same. The present invention also relates to an image display device having the hard coating film. Background Art

[0002] With the rapid progress of electronic devices such as displays, touch panels, and solar cells, devices are required to be thinner, lighter, and more flexible. In response to these requirements, the replacement of glass materials used in substrates, cover windows, etc. with plastic film materials is being studied. In these uses, plastic films are required to have high heat resistance, dimensional stability at high temperatures, and high mechanical strength. In addition, curved displays (flexible displays, foldable displays) are being developed in recent years, especially for plastic films used in cover windows, etc., in addition to the above-mentioned properties, excellent transparency and flexibility (bending resistance) are also required.

[0003] Patent Document 1 discloses a hard coat film in which a hard coat layer made of an acrylic material is provided on a polyethylene terephthalate film as a transparent substrate material for a flexible display.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-69197 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] For components arranged on the surface of a display such as a cover window, high hardness is required, and accordingly, a hard coating film having a hard coating layer with a large thickness is required. However, for a hard coating film made of an acrylic hard coating material, if the thickness of the hard coating layer is increased, warping (curling) of the film with the hard coating layer forming surface as the inner side will occur, and sometimes the handling of the film becomes difficult. In view of the above, an object of the present invention is to provide a hard coating film in which curling is suppressed even when the thickness of the hard coating layer is large.

[0009] Solutions for solving problems

[0010] The present inventors have found that the curling amount of the hard coat film can be controlled by applying a material having a negative cure shrinkage rate to the hard coat layer, thereby completing the present invention.

[0011] One embodiment of the present invention is a hard coating film having a hard coating layer on one main surface of a transparent resin film. The hard coating layer is formed by applying a hard coating composition on the main surface of the transparent resin film and irradiating the film with active energy rays.

[0012] Examples of the resin material of the transparent resin film include polyester, polycarbonate, polyamide, polyimide, cyclic polyolefin, acrylic resin, and cellulose resin. The thickness of the transparent resin film may be 10 to 150 μm.

[0013] The thickness of the hard coating layer is 0.15 times or more of the transparent resin film. The thickness of the hard coating layer may be 3 times or less of the transparent resin film. The thickness of the hard coating layer may be 2 to 150 μm.

[0014] As the hard coating composition, a hard coating composition having a negative curing shrinkage is used. The hard coating composition may include a polyorganosiloxane compound having an alicyclic epoxy group. The weight average molecular weight of the polyorganosiloxane compound may be 500 to 20,000.

[0015] The polyorganosiloxane compound having an alicyclic epoxy group is obtained, for example, by condensation of a silane compound having an alicyclic epoxy group. The hard coating composition may contain a photocationic polymerization initiator.

[0016] When the hard coating composition is cured on the transparent resin film, the active energy ray may be irradiated in a heated atmosphere. The heating temperature may be 45 to 150° C. The irradiation of the hard coating composition with active energy rays may be performed in a state where a support film is attached to the non-hard coating layer forming surface of the transparent resin film. After the hard coating composition is irradiated with active energy rays, heating may be further performed.

[0017] The absolute value of the curling amount of the hard coating film cut out into a square of 100 mm×100 mm is preferably 20 mm or less. The linear expansion coefficient of the hard coating layer may be larger than the linear expansion coefficient of the transparent resin film.

[0018] Effects of the Invention

[0019] According to the present invention, a hard coating film having a large hard coating layer thickness and small curling can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a cross-sectional view of the hard coating film.

[0021] Figure 2 It is a cross-sectional view of a laminated body in which a support film is bonded to a transparent resin film.

[0022] Figure 3 It is a cross-sectional view of a hard coating film laminated with a support film. DETAILED DESCRIPTION

[0023] [Overview of Hard Coat]

[0024] Figure 1It is a cross-sectional view of a laminated body according to one embodiment of the present invention. The laminated body 10 is a hard coating film including a hard coating layer 3 on one main surface 1A of a transparent resin film.

[0025] The transparent resin film 1 is a flexible film substrate as a base for forming a hard coat layer. The total light transmittance of the transparent resin film is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The haze of the transparent resin film is preferably 2% or less, and more preferably 1% or less.

[0026] The resin material constituting the transparent resin film is not particularly limited as long as it is a transparent resin. As the transparent resin, polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonate, polyamide, transparent polyimide, cyclic polyolefin, acrylic resins such as polymethyl methacrylate (PMMA), cellulose resins such as triacetyl cellulose (TAC), etc. can be cited.

[0027] Among them, polyesters such as PET and transparent polyimide are preferred from the perspective of high mechanical strength. When the hard coating film is used for the cover window of the display, the film substrate is required to have excellent heat resistance and mechanical strength, so transparent polyimide is particularly preferred as the resin material of the transparent resin film. Conventional fully aromatic polyimide is colored yellow or brown, but by introducing an alicyclic structure, a curved structure, a fluorine substituent, etc., a transparent polyimide with high visible light transmittance can be obtained.

[0028] The transparent resin film may be a single layer or a multilayer structure. For example, the transparent resin film may be a laminate formed by laminating a plurality of films, or may be a film having a functional layer such as an easy-adhesion layer, an antistatic layer, and an antireflection layer provided on the hard coating forming surface (first main surface 1A) and / or the hard coating non-forming surface (second main surface 1B).

[0029] The thickness of the transparent resin film is not particularly limited, but is preferably 10 μm or more, more preferably 30 μm or more, and further preferably 40 μm or more. The thickness of the transparent resin film is preferably 150 μm or less, more preferably 100 μm or less, further preferably 80 μm or less, and particularly preferably 60 μm or less. If the thickness of the transparent resin film is small, the mechanical properties such as the surface hardness of the hard coating are sometimes insufficient. On the other hand, if the thickness of the transparent resin film is large, the transparency and flexibility of the hard coating are sometimes reduced.

[0030] The thickness of the hard coating layer 3 is not particularly limited. From the viewpoint of surface hardness, it is preferably 2 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. It can be 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. From the viewpoint of transparency and flexibility (bending resistance), the thickness of the hard coating layer is preferably 150 μm or less, more preferably 100 μm or less, and further preferably 90 μm or less. It can be 80 μm or less or 70 μm or less.

[0031] The total thickness of the hard coating film, that is, the total thickness of the transparent resin film 1 and the thickness of the hard coating layer 3, is about 15 to 1000 μm, preferably 20 μm or more, more preferably 30 μm or more, further preferably 40 μm or more, and particularly preferably 50 μm or more. The total thickness of the hard coating film is preferably 250 μm or less, more preferably 170 μm or less, further preferably 150 μm or less, and particularly preferably 110 μm or less.

[0032] The ratio d2 / d1 of the thickness d2 of the hard coating layer 3 to the thickness d1 of the transparent resin film 1 is 0.15 or more, preferably 0.20 or more, more preferably 0.40 or more, and may be 0.60 or more, 0.80 or more, or 1.00 or more. Generally, if the thickness d2 of the hard coating layer is large and d2 / d1 is large, the curling of the hard coating layer tends to increase, but as described later, by using a hard coating material with a negative curing shrinkage, there is a tendency to reduce curling. The upper limit of the thickness ratio d2 / d1 is not particularly limited. From the viewpoint of the formability and flexibility of the hard coating layer, d2 / d1 is preferably 3.00 or less, more preferably 2.00 or less, and further preferably 1.80 or less, and may be 1.60 or less or 1.40 or less.

[0033] The linear expansion coefficient of the hard coating layer 3 is preferably greater than the linear expansion coefficient of the transparent resin film 1. The linear expansion coefficient is a calculated value from a TMA curve when cooling from a temperature of 100° C. to 30° C. by thermomechanical analysis (TMA). The linear expansion coefficient of the hard coating layer in the hard coating film is measured using a sample in which the transparent resin film is dissolved with a solvent or the like and the hard coating layer is separated.

[0034] By making the linear expansion coefficient of the hard coating layer relatively large, the stress generated at the interface between the hard coating layer and the transparent resin film when the hard coating material with a negative curing shrinkage rate is cured is eliminated by the stress generated at the interface due to the difference in linear expansion coefficient (difference in dimensional change due to heating), so that the curling of the hard coating film can be controlled to a desired value.

[0035] From the viewpoint of the stability of the curl control of the hard coat film, the difference in linear expansion coefficient between the transparent resin film and the hard coat layer is preferably 100 ppm / °C or less, preferably 70 ppm / °C or less, and more preferably 50 ppm / °C or less. The difference in linear expansion coefficient is preferably 5 ppm / °C or more, and may be 10 ppm / °C or more, 20 ppm / °C or more, or 30 ppm / °C or more.

[0036] The absolute value of the curling amount of the hard coating film, which is preferably cut out of a 100mm×100mm square sample, is less than 20mm at room temperature (25°C). For the curling amount of the hard coating film, the hard coating layer 3 is formed on the upper side and placed on a horizontal table for evaluation. The distance (floating amount) of the four vertices of the square from the table is measured, and the average value is taken as the curling amount. When the central part of the film surface floats (when reverse curling occurs), the hard coating layer is formed on the lower side, the film is placed on the table, and the curling amount is measured. In this case, the curling amount is a negative value.

[0037] When the hard coating material is photocationic curing, the acid generated as an active species by light irradiation of the photocationic polymerization initiator (photoacid generator) has a longer life than the photoradical, and the curing reaction continues for several days after light irradiation. As a result, the curling amount based on the dimensional change of the hard coating layer sometimes changes over time. In order to reduce the influence of the change over time, the curling amount adopts the measured value after 10 days of curing treatment (photocuring).

[0038] In the manufacturing process of displays etc. equipped with hard coating films, the hard coating films are sometimes cut into pieces of a predetermined size and then placed on a belt conveyor etc. for conveyance. At this time, if the downward curling amount is large, the end of the film may enter the gap between the conveyors and the film may fall from the conveyor. In addition, if the upward curling is large, when the hard coating film is fixed by suction from below for printing etc., the gap between the suction device and the film may be large, making it difficult to fix by suction.

[0039] Therefore, for the hard coating film, when the hard coating layer is provided on either the upper surface or the lower surface, the curling amount is preferably small. The absolute value of the curling amount of the hard coating film cut out of a 100 mm × 100 mm square is more preferably 15 mm or less, further preferably 10 mm or less, and can be 7 mm or less or 5 mm or less, and ideally 0.

[0040] In the present invention, a material having a negative curing shrinkage, that is, a material that expands and increases in volume due to curing, is used as the hard coating material. The curing shrinkage of the hard coating material is a volume shrinkage calculated by a density method in accordance with JIS K6901:2008 and is defined as follows. C is the density after curing, ρ LThe density of the liquid was measured by the pycnometer method, and the density of the solid was measured by the density gradient tube method.

[0041] Curing shrinkage (%) = 100 × (ρ C -ρ L ) / ρ C

[0042] Conventional hard coating materials such as acrylics have a positive curing shrinkage (shrinkage occurs as curing), so if the thickness of the hard coating increases, the compressive stress at the interface between the transparent resin film and the hard coating increases, and the warping (curling) of the film with the hard coating forming surface as the inner side tends to increase. In contrast, by making the hard coating material have a negative curing shrinkage, the curling with the hard coating forming surface as the inner side tends to be reduced.

[0043] On the other hand, if the curing shrinkage is too small (the volume expansion during curing is too large), the hard coating tends to curl with the hard coating forming surface as the outer side, and sometimes even if the difference in linear expansion coefficient between the transparent resin film and the hard coating is used, the curling cannot be properly controlled. Therefore, the curing shrinkage of the hard coating material is preferably -10% or more, more preferably -5% or more, and further preferably -3% or more. The curing shrinkage is preferably -0.01% or less, more preferably -0.1% or less, and further preferably -0.5% or less, and can be -1% or less or -1.5% or less.

[0044] [Hard coating]

[0045] A hard coating material (hard coating composition) containing a curable resin is applied to a transparent resin film and cured to form a hard coating layer. As described above, the hard coating material has a negative curing shrinkage. The curing shrinkage of the hard coating material mainly depends on the structure of the curable resin, in particular, the type of curable functional group. For example, a material having an alicyclic epoxy group as a curable functional group sometimes exhibits negative curing shrinkage due to photocationic polymerization.

[0046] Hereinafter, an embodiment in which a hard coating layer is formed from a hard coating material using a polyorganosiloxane compound having an alicyclic epoxy group as a resin material having a negative curing shrinkage rate will be described with reference to a specific example.

[0047] <Polyorganosiloxane compound>

[0048] (Silane compound)

[0049] The polyorganosiloxane compound having an alicyclic epoxy group is obtained by condensing a silane compound represented by the following general formula (1).

[0050] EBR 1 -Si(OR 3 ) xR 2 3-x … (1)

[0051] R 3 is a hydrogen atom or an alkyl group. The carbon number of the alkyl group is preferably 1 to 10. Specific examples of the alkyl group having 1 to 10 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, isopropyl, isobutyl, cyclohexyl, and ethylhexyl. x is 2 or 3.

[0052] The silane compound represented by the general formula (1) (hereinafter sometimes referred to as "silane compound (1)") has two or three (-OR 3 ).Si-OR 3 Since it is hydrolyzable, a polyorganosiloxane compound can be obtained by condensation of a silane compound. 3 The carbon number of R is preferably 3 or less. 3 A methyl group is particularly preferred.

[0053] R 2 It is a hydrogen atom or a monovalent hydrocarbon group selected from the group consisting of an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. Specific examples of hydrocarbons in the alkyl group and the aralkyl group include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, isopropyl, isobutyl, cyclohexyl, ethylhexyl, benzyl, phenyl, tolyl, xylyl, naphthyl, and phenethyl.

[0054] E in the general formula (1) is an alicyclic epoxy group. Since the alicyclic epoxy group maintains the alicyclic structure even when the epoxy group is ring-opened, the curing shrinkage is small and it is easy to show a negative curing shrinkage rate. The alicyclic epoxy group has an epoxy group composed of two adjacent carbon atoms and oxygen atoms that constitute the alicyclic ring. As the alicyclic ring, for example, a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cyclooctyl ring, etc. can be cited. Among them, from the viewpoint of structural stability and the reactivity of the epoxy group, as the alicyclic epoxy group, alicyclic epoxy groups having a six-membered ring alicyclic structure such as cyclohexene oxide (cyclohexene oxide), methyl cyclohexene oxide, etc. are preferred.

[0055] R 1 is an alkylene group having 2 to 12 carbon atoms, and B is a direct bond, an ether (-O-), or an ester (-COO-). That is, the silane compound of the general formula (1) is a silane compound having -BR as a spacer group on the Si atom. 1 - a compound having an alicyclic epoxy group bonded thereto. From the viewpoint of the curing reactivity of the alicyclic epoxy group, B is preferably directly bonded (i.e., the alicyclic epoxy group is directly bonded to the alkylene group R 1 ), or esters.

[0056] As alkylene R 1 Specific examples of R include dimethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, dodecamethylene, and the like. 1 , a part or all of the hydrogen atoms of the methylene group (-CH2-) may be substituted with a substituent having 1 to 6 carbon atoms. Examples of the substituent having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclohexyl, and phenyl.

[0057] If there is alkylene R 1 The larger the number of carbon atoms in the main chain and the longer the chain length, the greater the distance between the Si atom and the alicyclic epoxy group, and the tendency for the bending resistance of the hard coating after curing to be improved. 1 The smaller the carbon number of the main chain is, the higher the hardness of the hard coating layer tends to be.

[0058] Specific examples of the silane compound represented by the general formula (1) include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, γ-(3,4-epoxycyclohexyl)propyltrimethoxysilane, γ-(3,4-epoxycyclohexyl)propylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, γ-(3,4-epoxycyclohexyl)propyltriethoxysilane, and γ-(3,4-epoxycyclohexyl)propylmethyldiethoxysilane.

[0059] When a polyorganosiloxane compound is obtained by condensation of a silane compound, in addition to the silane compound having an alicyclic epoxy group represented by the general formula (1) above, other silane compounds may be used. Other silane compounds (i.e., silane compounds not containing an alicyclic epoxy group, hereinafter sometimes referred to as "silane compound (2)") are represented by the following general formula (2).

[0060] R 4 -(Si(OR 3 ) x R 2 3-x )… (2)

[0061] In the general formula (2), R 2 , R 3 and x are the same as in the general formula (1). 4 It is a monovalent organic group not containing an alicyclic epoxy group. 4It is a group containing a substituted or unsubstituted double bond (for example, a substituted or unsubstituted alkenyl group having 1 to 10 carbon atoms), a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, an aralkyl group having 7 to 12 carbon atoms, a group having a glycidyl group, a group having an oxetanyl group, or a hydrogen atom.

[0062] When the polyorganosiloxane compound is obtained by condensation of silane compounds, the ratio of the silane compound (1) to the total of the silane compound (1) and the silane compound (2) is preferably 33 to 100 mol%, more preferably 50 to 100 mol%. The ratio of the silane compound (1) may be 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more, or 95 mol% or more, or 100 mol%.

[0063] (Characteristics of polyorganosiloxane compounds)

[0064] Through the Si-OR 3 Partial hydrolysis and condensation form Si-O-Si bonds between silane compounds to generate polyorganosiloxane compounds. From the viewpoint of increasing the hardness of the cured film (hard coat), the weight average molecular weight of the polyorganosiloxane compound is preferably 500 or more. In addition, from the viewpoint of suppressing volatilization, the weight average molecular weight of the polyorganosiloxane compound is also preferably 500 or more. On the other hand, if the molecular weight is too large, turbidity sometimes occurs due to reduced compatibility with other compositions. Therefore, the weight average molecular weight of the polyorganosiloxane compound is preferably 20,000 or less. The weight average molecular weight of the polyorganosiloxane compound is more preferably 700 to 18,000, further preferably 1,000 to 16,000, and can be 1,200 to 14,000, or 1,500 to 12,000.

[0065] The weight average molecular weight of the polyorganosiloxane compound can be controlled by appropriately selecting the amount of water, the type and amount of the catalyst used in the reaction. For example, the more water is added together with the catalyst during the hydrolysis reaction, the larger the weight average molecular weight tends to be.

[0066] The polyorganosiloxane compound produced by the hydrolysis and condensation of the silane compound of the general formula (1) contains a structural unit represented by the following formula (3) and a structural unit represented by the following formula (4).

[0067] [EBR 1 -SiO 3 / 2 ]… (3)

[0068] [EBR 1 -SiO 2 / 2 -D]… (4)

[0069] In the general formula (3) and the general formula (4), E, ​​B and R 1 The same as in general formula (1). D in general formula (4) is a hydrogen atom or a group selected from the group consisting of an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms.

[0070] The structural unit represented by formula (3) is: three alkoxy groups (Si-OR 3 ) all undergo condensation reaction to form a Si-O-Si bond, which is called a "T3 body". The structural unit represented by formula (4) is a structure in which two of the three alkoxy groups of the silane compound having a T unit structure with x=3 in the general formula (1) undergo condensation reaction to form a Si-O-Si bond, which is called a "T2 body".

[0071] There is a tendency that the smaller the ratio [T3 form] / [T2 form] of the structure (T3 form) represented by formula (3) to the structure (T2 form) represented by formula (4), the higher the bending resistance of the hard coating obtained by curing the polyorganosiloxane compound. From the viewpoint of obtaining a hard coating film in which cracks and breakages of the hard coating layer are suppressed when bent, the ratio of the T3 form to the T2 form of the polyorganosiloxane compound (hereinafter sometimes described as "T3 / T2 ratio") may be less than 5, or may be 4 or less, 3.5 or less, 3 or less, or 2.5 or less. From the viewpoint of ensuring the hardness of the hard coating layer, the T3 / T2 ratio of the polyorganosiloxane compound may be 0.8 or more, or 1 or more, 1.5 or more, or 2 or more.

[0072] The content and ratio of the T3 form and the T2 form in the polyorganosiloxane compound can be 29 It was calculated by Si-NMR measurement. 29 In Si-NMR, Si atoms in the T3 form and Si atoms in the T2 form show different chemical shifts, so the T3 / T2 ratio can be calculated from the ratio of the integrated values ​​of the respective signals in the NMR spectrum.

[0073] The T3 / T2 ratio can be controlled by adjusting the amount of water, the type of catalyst, and the amount of catalyst used in the hydrolysis-condensation reaction of the silane compound. For example, the greater the amount of catalyst, the greater the T3 / T2 ratio. As described later, by using a neutral salt catalyst, there is a tendency for T3 / T2 to become smaller.

[0074] (Hydrolysis and condensation of silane compounds)

[0075] By reacting the silane compound with water, the Si-OR 3The amount of water required for the hydrolysis and condensation reaction is 1:1 relative to the -OR bonded to the Si atom. 3 The amount of water is preferably 0.3 to 3 equivalents, and more preferably 0.5 to 2 equivalents. When the amount of water is too small, the OR 3 If the amount of water is too high, the molecular weight of the polyorganosiloxane compound is small, so the hardness of the hard coat tends to be insufficient. If the amount of water is too high, the reaction rate of the hydrolysis and condensation reaction is high, and a high molecular weight condensate is generated, which tends to reduce the transparency and flexibility of the hard coat.

[0076] In the hydrolysis reaction and condensation reaction of the silane compound, it is preferred to suppress the deactivation caused by the ring opening of the alicyclic epoxy group contained in the silane compound (1). From the viewpoint of suppressing the ring opening of the epoxy group, it is preferred to carry out the reaction under neutral or alkaline conditions. In particular, from the viewpoint of reducing the T3 / T2 ratio of the polyorganosiloxane compound obtained as a condensate of the silane compound, it is preferred to carry out the hydrolysis and condensation reaction in the presence of a neutral salt catalyst.

[0077] Neutral salts are normal salts of strong acids and strong bases, specifically, salts of ions (cations) of elements selected from the group consisting of alkali metal elements and Group 2 elements and halide ions (anions) selected from the group consisting of chloride ions, bromide ions, and iodide ions.

[0078] Specific examples of the neutral salt include lithium chloride, sodium chloride, potassium chloride, beryllium chloride, magnesium chloride, calcium chloride, lithium bromide, sodium bromide, potassium bromide, beryllium bromide, magnesium bromide, calcium bromide, lithium iodide, sodium iodide, potassium iodide, beryllium iodide, magnesium iodide, and calcium iodide.

[0079] As described above, by using a neutral salt catalyst, a polyorganosiloxane compound with a small T3 / T2 ratio can be obtained. In addition, in the case of an acid catalyst or a base catalyst, the catalyst itself undergoes an electrophilic / nucleophilic reaction with various substances, and a neutral salt has low corrosiveness to metal and resin materials of a reaction container or a storage container, so there is an advantage that there are few restrictions on the materials of the manufacturing / storage equipment.

[0080] When the alkaline catalyst commonly used in the condensation reaction of the silane compound remains in the hard coating composition, the acid generated by the photocationic polymerization initiator (photoacid generator) is sometimes quenched to hinder the polymerization reaction. In contrast, by using a neutral salt catalyst, polymerization hindrance can be suppressed. Therefore, the neutral salt catalyst can remain in the polyorganosiloxane compound and the hard coating composition obtained by the condensation of the silane compound, and the steps of removing and neutralizing the catalyst after the reaction can be omitted. The use of a neutral salt catalyst helps to simplify the manufacturing process and improve the yield.

[0081] The amount of the catalyst is not particularly limited. The more the amount of the catalyst is used, the more the hydrolysis and condensation reaction of the silane compound tends to be promoted. On the other hand, if the amount of the catalyst is too much, the transparency of the condensate is sometimes impaired, or the purification becomes complicated. The amount of the neutral salt catalyst used is relatively large relative to the hydrolyzable silyl group (-OR 3 )1 mol, preferably 0.000001 to 0.1 mol, more preferably 0.000005 to 0.01 mol.

[0082] As described above, a neutral salt catalyst may remain in the polyorganosiloxane compound obtained by the hydrolysis and condensation reaction of the silane compound. The amount of the neutral salt (catalyst) remaining in the polyorganosiloxane compound may be 1 ppm or more, 10 ppm or more, 50 ppm or more, or 100 ppm or more. From the viewpoint of the transparency of the hard coat layer, the amount of the alkaline catalyst remaining in the polyorganosiloxane compound is preferably 10000 ppm or less, more preferably 5000 ppm or less, further preferably 3000 ppm or less, and may be 1000 ppm or less, 800 ppm or less, or 500 ppm or less.

[0083] In the hydrolysis and condensation reaction of the silane compound, the reaction can be carried out while the diluent solvent and the alcohol etc. produced by the hydrolysis are refluxed. The diluent solvent preferably exhibits compatibility with water, and preferably a water-soluble alcohol or ether compound. Since most silane compounds have low compatibility with neutral salts and water used in the hydrolysis, it is preferred to react by making a solution with the diluent solvent in the form of a compatible system.

[0084] The boiling point of the dilution solvent is preferably 40° C. or higher, more preferably 50° C. or higher, and further preferably 60° C. or higher. If the boiling point of the dilution solvent is too low, the dilution solvent may be in a reflux state at low temperatures, thereby reducing the reaction rate. From the viewpoint of the removability of the dilution solvent after the reaction, the boiling point of the dilution solvent is preferably 200° C. or lower.

[0085] Specific examples of the diluting solvent include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, 1-methoxy-2-propanol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol dimethyl ether and the like.

[0086] The reaction temperature of the hydrolysis and condensation reaction of the silane compound is preferably 40° C. or higher, more preferably 50° C. or higher, and further preferably 60° C. or higher. When the reaction temperature is 40° C. or higher, the catalyst activity of the neutral salt is high, so the reaction time can be shortened. From the viewpoint of suppressing the side reaction of the organic group of the silane compound, the reaction temperature is preferably 200° C. or lower.

[0087] From the viewpoint of increasing the crosslinking point density of the cured product (hard coating) and thus increasing the hardness, the polyorganosiloxane compound obtained by hydrolysis and condensation of the silane compound preferably has a high residual rate of alicyclic epoxy groups. The residual rate of alicyclic epoxy groups, that is, the ratio of the number of moles of alicyclic epoxy groups in the polyorganosiloxane compound obtained by condensation to the number of moles of alicyclic epoxy groups contained in the silane compound (1) as a raw material, is preferably 20% or more, more preferably 40% or more, further preferably 60% or more, particularly preferably 80% or more, and can be 90% or more or 95% or more. The residual rate of alicyclic epoxy groups is determined by 1 It was determined by H-NMR measurement.

[0088] In the hydrolysis and condensation reactions, in addition to the side reactions such as the ring opening of the epoxy group, the EBR bonded to the Si atom of the silane compound (1) 1 - does not react and maintains its structure. Therefore, the polyorganosiloxane compound obtained by condensation of the silane compound (1) has a structure represented by the following general formula (5) (hereinafter sometimes referred to as "structure (5)").

[0089] [EBR 1 -Si]… (5)

[0090] E, B and R in the general formula (5) 1 This is the same as the general formula (1). That is, the structure (5) is a structure in which an alicyclic epoxy group is bonded to a Si atom via or without another organic group.

[0091] The ratio of the number of structures (5) of the polyorganosiloxane compound (i.e., the number of alicyclic epoxy groups) to the total number of Si atoms is preferably 33% or more, more preferably 50% or more, and can be 60% or more, 70% or more, 80% or more, 90% or more, or 95% or more, and can also be 100%.

[0092] Since each silane compound (1) and the silane compound (2) has one Si atom per molecule, the polyorganosiloxane compound generated by the condensation of N molecules of the silane compound contains N Si atoms. When the alicyclic epoxy group remains without reacting during the hydrolysis and condensation reaction, n structures (5) are generated from n silane compounds (1). Therefore, in the polyorganosiloxane compound obtained by the condensation of the silane compounds, the ratio of the silane compound (1) in the silane compound used as the raw material (molar ratio: n / N) is approximately equal to the ratio of the structure (5) to the number of Si atoms in the polyorganosiloxane compound.

[0093] When the silane compound (2) is used as the silane compound in addition to the silane compound (1), the polyorganosiloxane compound has a structure represented by the following general formula (6) (hereinafter sometimes referred to as "structure (6)") in addition to the above structure (5).

[0094] [R 4 -Si]… (6)

[0095] R in the general formula (6) 4 The same as the general formula (2).

[0096] <Hard Coating Composition>

[0097] The hard coating composition is a composition containing the above-mentioned curable resin. The hard coating composition preferably contains a photopolymerization initiator in addition to the curable resin such as a polyorganosiloxane compound, and may contain other components.

[0098] (Photocationic polymerization initiator)

[0099] When the curable resin is a polyorganosiloxane compound having an epoxy group, the hard coating composition preferably contains a photocationic polymerization initiator. The photocationic polymerization initiator is a compound (photoacid generator) that generates an acid by irradiation with active energy rays. The acid generated by the photoacid generator is used to perform ring-opening and polymerization reactions of the epoxy group of the polyorganosiloxane compound to form intermolecular crosslinks, and the hard coating material is cured.

[0100] Examples of the photoacid generator include strong acids such as toluenesulfonic acid and boron tetrafluoride; onium salts such as sulfonium salts, ammonium salts, phosphonium salts, iodonium salts, and selenium salts; iron-arene complexes; silanol-metal chelate complexes; sulfonic acid derivatives such as disulfones, disulfonyldiazomethanes, disulfonylmethanes, sulfonylbenzoylmethanes, imide sulfonates, and benzoin sulfonates; and organic halogen compounds.

[0101] Among the above-mentioned photoacid generators, aromatic sulfonium salts or aromatic iodonium salts are preferred from the perspective of high stability of the hard coating composition containing a polyorganosiloxane compound having an alicyclic epoxy group. As their counter anions, fluorophosphate anions, fluoroantimonate anions, fluoroborate anions, etc. can be cited. When a photoacid generator containing these counter anions is used, the photocuring speed is high, and a hard coating layer with excellent adhesion to a transparent resin film is easily obtained.

[0102] The content of the photocationic polymerization initiator in the hard coating composition is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and further preferably 0.2 to 2 parts by weight, based on 100 parts by weight of the polyorganosiloxane compound.

[0103] (Leveling agent)

[0104] The hard coating composition may include a leveling agent. By including a leveling agent in the hard coating, it is expected that the surface tension will be reduced, the surface smoothness will be improved, the sliding property will be improved, the antifouling property (anti-fingerprint property, etc.) will be improved, etc. In addition, by including a group reactive with an epoxy group and / or a hydrolysis-condensation group in the leveling agent, it is expected that the scratch resistance of the hard coating will be improved.

[0105] As the leveling agent, there can be mentioned silicone leveling agents, fluorine leveling agents, etc. As the silicone leveling agent, there can be mentioned a leveling agent having a polysiloxane skeleton. As the fluorine leveling agent, there can be mentioned a leveling agent having a fluoroaliphatic hydrocarbon skeleton. As the fluoroaliphatic hydrocarbon skeleton, there can be mentioned fluoromethane, fluoroethane, fluoropropane, fluoroisopropylane, fluorobutane, fluoroisobutylane, fluorotert-butane, fluoropentane, fluorohexane and the like fluoroC 1-10 Alkanes, etc.

[0106] When the hard coating composition contains a leveling agent, the content thereof is preferably 0.001 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, and further preferably 0.05 to 1 part by weight or less, based on 100 parts by weight of the polyorganosiloxane compound.

[0107] (Reactive diluent)

[0108] The hard coating composition may contain a reactive diluent. The reactive diluent may contain, for example, a cationically polymerizable compound other than the above-mentioned polyorganosiloxane compound. As a reactive diluent for photocationic polymerization, a compound having a cationically polymerizable functional group is used. Examples of the cationically polymerizable functional group of the reactive diluent include an epoxy group, a vinyl ether group, an oxetane group, and an alkoxysilyl group. Among them, from the aspect of high reactivity with the epoxy group of the polyorganosiloxane compound, as a reactive diluent, it is preferred to have an epoxy group.

[0109] The content of the reactive diluent in the hard coating composition is preferably 100 parts by weight or less, more preferably 50 parts by weight or less, based on 100 parts by weight of the polyorganosiloxane compound.

[0110] (Photosensitizer)

[0111] The hard coating composition may include a photosensitizer for the purpose of improving the photosensitivity of the photocationic polymerization initiator (photoacid generator). For photosensitizers, since photosensitizers that can absorb light in a wavelength region that the photoacid generator itself cannot absorb are more effective, photosensitizers that overlap less with the absorption wavelength region of the photoacid generator are preferred. Examples of photosensitizers include anthracene derivatives, benzophenone derivatives, thioxanthone derivatives, anthraquinone derivatives, and benzoin derivatives.

[0112] The content of the photosensitizer in the hard coating composition is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and further preferably 10 parts by weight or less, based on 100 parts by weight of the photoacid generator.

[0113] (Particles)

[0114] For the purpose of adjusting the film properties such as surface hardness and bending resistance, inhibiting the curing shrinkage, etc., the hard coating composition may contain particles. As particles, organic particles, inorganic particles, organic-inorganic composite particles, etc. can be appropriately selected and used. As materials for organic particles, poly(meth) alkyl acrylates, cross-linked poly(meth) alkyl acrylates, cross-linked styrene, nylon, silicone, cross-linked silicone, cross-linked urethane, cross-linked butadiene, etc. can be cited. As materials for inorganic particles, metal oxides such as silicon dioxide, titanium dioxide, aluminum oxide, tin oxide, zirconium oxide, zinc oxide, and antimony oxide can be cited; metal nitrides such as silicon nitride and boron nitride; metal salts such as calcium carbonate, calcium hydrogen phosphate, calcium phosphate, and aluminum phosphate can be cited. As organic-inorganic composite fillers, those having an inorganic layer formed on the surface of organic particles can be cited, and those having an organic layer or organic microparticles formed on the surface of inorganic particles can also be cited.

[0115] The particle shape includes spherical, powdery, fibrous, needle-like, flaky, etc. Spherical particles have no anisotropy and are less likely to have uneven stress, thus suppressing deformation and helping to suppress curling caused by volume change during hard coating material curing.

[0116] The average particle size of the particles is, for example, about 5 nm to 10 μm. From the viewpoint of improving the transparency of the hard coat layer, the average particle size is preferably 1000 nm or less, more preferably 500 nm or less, further preferably 300 nm or less, and particularly preferably 100 nm or less. The particle size can be measured by a laser diffraction / scattering particle size distribution measuring device, with the volume-based median particle size as the average particle size.

[0117] The hard coating composition may contain particles that have been surface-modified. The surface modification of the particles tends to improve the dispersibility of the particles in the polyorganosiloxane compound. In addition, when the particle surface is modified with a polymerizable functional group that can react with an epoxy group, the functional group on the particle surface reacts with the epoxy group of the polyorganosiloxane compound to form a chemical crosslink, so that it can be expected that the film strength will be improved.

[0118] Examples of polymerizable functional groups that can react with epoxy groups include vinyl, (meth)acryloyl, hydroxyl, phenolic hydroxyl, carboxyl, anhydride, amino, epoxy, and oxetane. Among them, epoxy is preferred. In particular, particles surface-modified with epoxy are preferred because chemical crosslinks can be formed between the particles and the polyorganosiloxane compound during curing of the hard coating composition based on photocationic polymerization.

[0119] Examples of particles having a reactive functional group on the surface include surface-modified inorganic particles and core-shell polymer particles.

[0120] (Solvent)

[0121] The hard coating composition may be a solvent-free type or may contain a solvent. When a solvent is contained, it is preferred that the transparent resin film is not dissolved. On the other hand, by using a solvent having a solubility to the extent that the transparent resin film swells, the adhesion between the transparent resin film and the hard coating layer is sometimes improved. The content of the solvent is preferably 500 parts by weight or less, more preferably 300 parts by weight or less, and further preferably 100 parts by weight or less relative to 100 parts by weight of the polyorganosiloxane compound.

[0122] (additive)

[0123] The hard coating composition may contain additives such as inorganic pigments, organic pigments, surface regulators, surface modifiers, plasticizers, dispersants, wetting agents, thickeners, defoamers, etc. In addition, the hard coating composition may contain thermoplastic or thermosetting resin materials other than the above-mentioned polyorganosiloxane compound. When the polyorganosiloxane compound and / or the resin material other than the polyorganosiloxane compound has free radical polymerizability, the hard coating composition may contain a free radical polymerization initiator in addition to the photocationic polymerization initiator.

[0124] <Formation of Hard Coat Layer>

[0125] The hard coating composition is applied onto a transparent resin film, and after the solvent is dried and removed as necessary, the hard coating composition is cured by irradiating with active energy rays, thereby obtaining a hard coating film having the hard coating layer 3 on the transparent resin film 1 .

[0126] Before applying the hard coating composition, the surface of the transparent resin film may be subjected to a surface treatment such as a corona treatment or a plasma treatment. In addition, an easy-adhesion layer (primer layer) or the like may be provided on the surface of the transparent resin film. The hard coating layer formed by curing the polyorganosiloxane compound exhibits high adhesion to the resin film, so an easy-adhesion layer or the like may not be provided. That is, in the hard coating film, the transparent resin film 1 and the hard coating layer 3 may be in contact with each other.

[0127] Before applying the hard coating composition to the first main surface 1A of the transparent resin film 1, Figure 2 As shown, the support film 6 can be bonded to the second main surface 1B of the transparent resin film 1. The support film 6 is preferably releasable from the transparent resin film 1, and for example, a laminate having a weakly adhesive pressure-sensitive adhesive layer 4 on the surface of the film 5 can be used.

[0128] The hard coating composition is applied to the first main surface 1A of the transparent resin film and cured in a state where the support film 6 is bonded to the second main surface 1B of the transparent resin film. Figure 3 As shown in FIG. 1 , a laminated body having a hard coating film and a support film 6 is formed. The support film is peeled off and removed from the laminated body, thereby obtaining Figure 1 The hard coating film 10 is shown.

[0129] By forming the hard coating layer 3 in a state of being bonded with the support film 6, the deformation and heat loss of the transparent resin film during heating or light irradiation can sometimes be suppressed. In addition, by bonding the support film 6, the overall thickness becomes larger and the rigidity of the laminate 12 increases, so the generation of curling during the formation of the hard coating layer can be suppressed, and the handling property is improved.

[0130] From the viewpoint of providing rigidity to the laminate 12 of the transparent resin film 1 and the support film 6, the thickness of the support film 6 is preferably greater than the thickness of the transparent resin film 1. The thickness of the support film 6 is preferably 50 μm or more, more preferably 80 μm or more, and further preferably 100 μm or more. From the viewpoint of maintaining the handling properties during roll conveyance, etc., the thickness of the support film is preferably 500 μm or less, more preferably 300 μm or less, and may be 200 μm or less or 150 μm or less.

[0131] The method for coating the hard coating composition onto the transparent resin film is not particularly limited, and a known method can be used. Examples of the coating method include die coaters such as fountain dies and slot dies, roll coaters such as gravure coaters and comma coaters, rod coaters, dip coaters, spin coaters, and spray coaters.

[0132] Examples of active energy rays irradiated during photocuring include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams. Ultraviolet rays are preferred as active energy rays because of their high curing reaction speed and excellent energy efficiency. The cumulative irradiation amount of active energy rays is, for example, 50 to 10,000 mJ / cm 2 The thickness of the hard coat layer can be set according to the type and amount of the photocationic polymerization initiator, the thickness of the hard coat layer, and the like.

[0133] When the hard coating composition containing the polyorganosiloxane compound is irradiated with active energy rays, the alicyclic epoxy radical undergoes ring-opening and cationic polymerization by the acid generated by the photocationic polymerization initiator, and is cured to obtain a hard coating layer containing a cured resin having a structure represented by the following general formula (7).

[0134] [ABR 1 -Si(O 1 / 2 ) x R 2 3-x ]… (7)

[0135] A in formula (7) is an alicyclic structure obtained by reacting an alicyclic epoxy group. The carbon number of A may be 7 or less. As a structure having a carbon number of 7 or less, the exemplary formula C6H9(OH)(O 1 / 2 ) and the exemplary formula C6H8(OH)(O 1 / 2 Among them, the preferred structure is the structure represented by C6H9(OH)(O 1 / 2 ) shown in the structure.

[0136] The hard coat layer obtained by curing the polyorganosiloxane compound contains a structural unit represented by the following formula (8) and a structural unit represented by the following formula (9).

[0137] [ABR 1 -SiO 3 / 2 ]… (8)

[0138] [ABR 1 -SiO 2 / 2 -D]… (9)

[0139] In the general formulae (8) and (9), A is the same as in the general formula (7). In the general formulae (7) to (9), B, R 1 and D are the same as those in general formula (1), (3), and (4). The SiO bond network of the polysiloxane compound is maintained even after curing by the reaction of the alicyclic epoxy group of the polysiloxane compound, so the ratio (T3 / T2 ratio) of the structure (T3 body) represented by formula (8) to the structure (T2 body) represented by formula (9) is equal to the T3 / T2 ratio of the polysiloxane compound before curing.

[0140] The polyorganosiloxane compound comprises a structure derived from the silane compound (2), and R 4When epoxy groups other than alicyclic epoxy groups are contained, in addition to the reaction between alicyclic epoxy groups derived from the silane compound (1), the reaction between alicyclic epoxy groups derived from the silane compound (1) and epoxy groups derived from the silane compound (2), and the reaction between epoxy groups derived from the silane compound (2) occur.

[0141] The polyorganosiloxane compound having an alicyclic epoxy group forms a bond between two alicyclic rings by reaction of the alicyclic epoxy group, so the molecular volume is easily increased by curing. The hard coating composition has a negative curing shrinkage, so the curing shrinkage is smaller than that of a conventional acrylic hard coating material, and the curling of the hard coating film can be reduced.

[0142] When the linear expansion coefficient of the hard coating layer is larger than that of the transparent resin film, by making the temperature during irradiation with active energy rays higher than room temperature, the stress at the interface between the hard coating layer and the transparent resin film caused by negative curing shrinkage (volume expansion) is eliminated by the difference in linear expansion coefficients between the hard coating layer and the transparent resin film (the difference in shrinkage when returning to room temperature from a heated state), thereby enabling the curling amount to be appropriately controlled.

[0143] From the viewpoint of reducing the curling amount, the temperature during the active energy ray irradiation is preferably 35° C. or higher, more preferably 45° C. or higher, and further preferably 50° C. or higher, and may be 55° C. or higher or 60° C. or higher. From the viewpoint of suppressing the plastic deformation of the transparent resin film caused by heat, the temperature during the active energy ray irradiation is preferably 150° C. or lower, more preferably 120° C. or lower, and may be 100° C. or lower, 90° C. or lower, or 85° C. or lower.

[0144] The acid, which is an active species of photocationic polymerization, remains in the composition even after irradiation with active energy rays, and has a low reaction rate at low temperatures near room temperature. Therefore, sometimes after irradiation with active energy rays, the curing reaction will also proceed for several days, and the curl of the hard coating will gradually change. In such a case, by estimating the amount of curl change over time and implementing irradiation with active energy rays, a hard coating with smaller curl can also be obtained.

[0145] The hard coating composition has a negative curing shrinkage, so if it is cured, tensile stress is generated at the interface between the hard coating and the transparent resin film, and the force of curling with the hard coating forming surface as the outside is exerted. If the temperature during the active energy ray irradiation is set to be relatively high and the photocuring is performed under the condition that the thermal expansion of the hard coating is large, the shrinkage of the hard coating is large when it is restored to room temperature, so it is easy to produce curling with the hard coating forming surface as the inside. Thereafter, if it is cured over time at room temperature, negative curing shrinkage (volume expansion) occurs in the hard coating, so the curling is relaxed over time, and a hard coating with a small amount of curling is obtained.

[0146] Heating can be performed after irradiation with active energy rays. Heating can increase the curing speed and reduce the amount of uncured materials, so that the change in the amount of curling over time can be suppressed. In addition, it is also possible to expect an increase in the hardness of the hard coating layer caused by an increase in the curing rate. In the case of heating after irradiation with active energy rays, the heating temperature is, for example, 35°C or more, preferably 50°C or more, more preferably 70°C or more, 80°C or more, and can be 90°C or more or 100°C or more. From the viewpoint of suppressing the plastic deformation of the hard coating film, the heating temperature is preferably 180°C or less, more preferably 150°C or less. The heating time is, for example, about 10 seconds to 60 minutes, and can be 20 seconds or more, 30 seconds or more, 40 seconds or more, 50 seconds or more, or 60 seconds or more, or 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, or 5 minutes or less.

[0147] [Characteristics of hard coating]

[0148] The hard coating layer having a polymer matrix cross-linked by ring-opening and polymerization reaction of the alicyclic epoxy groups of the polyorganosiloxane compound can achieve a surface hardness comparable to that of glass. The surface hardness (pencil hardness) of the hard coating layer forming surface of the hard coating film is preferably 2H or more, more preferably 4H or more, and can be 6H or more, 7H or more, or 8H or more.

[0149] The hard coating film is preferably such that when a cylindrical mandrel test is performed with the hard coating formed surface as the inner side, the diameter of the mandrel at which cracks occur in the hard coating is When the thickness of the hard coating layer is the same, the smaller the diameter of the core rod, the better the bending resistance. The diameter of the core rod where cracks occur in the hard coating layer is preferably 3 mm or less, more preferably 2 mm or less. As described above, the smaller the T3 / T2 ratio of the polyorganosiloxane compound, the better the bending resistance. The tendency to become smaller.

[0150] The total light transmittance of the hard coat film is preferably 80% or more, more preferably 85% or more, and further preferably 89% or more.

[0151] [Application of hard coating]

[0152] The hard coating film may have various functional layers on the hard coating layer 3 or on the second main surface 1B of the transparent resin film 1. In addition, a functional layer may be provided between the transparent resin film 1 and the hard coating layer 3. Examples of the functional layer include an adhesion-imparting layer, an adhesive bonding layer, an antireflection layer, a water-repellent layer, an oil-repellent layer, a transparent conductive layer, a refractive index adjusting layer, an antistatic layer, an antiglare layer, and a polarizer-containing layer.

[0153] The hard coating film of the present invention can be suitably used for a cover window provided on the surface of an image display panel, a transparent substrate for a display, a transparent substrate for a touch panel, a substrate for a solar cell, etc. The hard coating film of the present invention is particularly suitable for use as a cover window or substrate film for curved displays, flexible displays, etc.

[0154] Example

[0155] Hereinafter, the present invention will be described in more detail by showing an example of producing a hard coating film having a hard coating layer on a transparent resin film. However, the present invention is not limited to the following example.

[0156] [Transparent resin film]

[0157] <Synthesis of Polyimide Resin>

[0158] Dimethylformamide (DMF) was added to a reaction container and stirred under a nitrogen atmosphere. Diamine and tetracarboxylic dianhydride were added thereto at the molar ratio shown in Table 1 and stirred for 5 to 10 hours under a nitrogen atmosphere to react and obtain a polyamic acid solution having a solid content concentration of 18%.

[0159] Pyridine was added as an imidization catalyst to the polyamic acid solution. After complete dispersion, acetic anhydride was added as a dehydrating agent and stirred at 90°C for 3 hours. After the reaction solution was cooled to room temperature, isopropyl alcohol (IPA) was added dropwise while stirring to precipitate the polyimide resin. After filtering and washing with IPA, vacuum drying was performed to obtain polyimide resin A and polyimide resin B.

[0160] The charging ratio (molar ratio) of the monomers (diamine and tetracarboxylic dianhydride) used for preparing the polyimide resin A (PI-A) and the polyimide resin B (PI-B) is shown in Table 1. The abbreviations of the monomers in Table 1 are as follows.

[0161] TFMB: 2,2'-bis(trifluoromethyl)benzidine

[0162] 3,3'-DDS: 3,3'-diaminodiphenyl sulfone

[0163] TMHQ: p-phenylene trimellitic dianhydride

[0164] 6FDA: 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropionic dianhydride

[0165] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0166] CBDA: 1,2,3,4-cyclobutanetetracarboxylic dianhydride

[0167] Tahmbp: 2,2',3,3',5,5'-hexamethyl-biphenyltetracarboxylic dianhydride

[0168] [Table 1]

[0169]

[0170] <Polyimide film 1>

[0171] The polyimide resin A was dissolved in dichloromethane to prepare a solution with a solid content concentration of 11 wt%. The dichloromethane solution was applied to an alkali-free glass plate and dried at 40°C for 60 minutes, 70°C for 30 minutes, 150°C for 30 minutes, 170°C for 30 minutes, and 200°C for 60 minutes in an air atmosphere to obtain a polyimide film 1 with a thickness of 50 μm. The linear expansion coefficient of the polyimide film 1 (PI1) obtained from the TMA curve when the temperature was raised to 100°C and then cooled to 30°C at 5°C / min by thermomechanical analysis (TMA) was 30 ppm / °C.

[0172] <Polyimide film 2>

[0173] A polyimide film 2 having a thickness of 35 μm was obtained in the same manner as in the preparation of the polyimide film 1 except that the coating thickness of the solution was changed. The linear expansion coefficient of the polyimide film 2 (PI2) was 30 ppm / °C.

[0174] <Polyimide film 3>

[0175] A polyimide film 3 having a thickness of 30 μm was obtained in the same manner as in the preparation of the polyimide film 1 except that the polyimide resin B was used instead of the polyimide resin A and the coating thickness of the solution was changed. The linear expansion coefficient of the polyimide film 3 (PI3) was 16 ppm / °C.

[0176] <Polyethylene terephthalate film 1>

[0177] A thick polyethylene terephthalate film ("Lumirror U48" manufactured by Toray Industries, Inc.) having a thickness of 125 μm was used. The linear expansion coefficient of the polyethylene terephthalate film 1 (PET1) was 15 ppm / °C.

[0178] <Polyethylene terephthalate film 2>

[0179] A polyethylene terephthalate film having a thickness of 50 μm ("Lumirror U48" manufactured by Toray Industries, Inc.) was used. The linear expansion coefficient of the polyethylene terephthalate film 2 (PET2) was 15 ppm / °C.

[0180] [Synthesis of polyorganosiloxane compounds]

[0181] <Synthesis example 1>

[0182] In a reaction vessel equipped with a thermometer, a stirring device, and a reflux condenser, 66.5 g (270 mmol) of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane ("SILQUEST A-186" manufactured by Momentive Performance Materials Inc.) and 16.5 g of 1-methoxy-2-propanol (PGME) were added and stirred evenly. A solution of 0.039 g (0.405 mmol) of magnesium chloride as a catalyst dissolved in a mixture of 9.7 g (539 mmol) of water and 5.8 g of methanol was added dropwise to the mixture for 5 minutes and stirred until it became uniform. Thereafter, the temperature was raised to 80°C, and a polycondensation reaction was carried out for 6 hours while stirring. After the reaction was completed, the solvent and water were distilled off using a rotary evaporator to obtain a polyorganosiloxane compound A.

[0183] Using a Bruker NMR (400 MHz), the 1 The H-NMR spectrum confirmed that the residual rate of epoxy groups in the polyorganosiloxane compound 1 was 95% or more. The weight average molecular weight in terms of polystyrene measured using a GPC apparatus "HLC-8220GPC" manufactured by Tosoh Corporation (columns: TSKgel GMHXL×2, TSKgel G3000HXL, TSKgel G2000HXL) with THF as the solvent was 3000. The H-NMR spectrum was measured using an Agilent NMR (600 MHz) 29 The ratio T3 / T2 (molar ratio) of the T3 form to T2 determined by Si-NMR spectrum was 2.3. The residual amount of magnesium chloride (neutral salt catalyst) in the polyorganosiloxane compound 1 calculated based on the charge amount was 814 ppm.

[0184] <Synthesis example 2>

[0185] In a reaction vessel equipped with a thermometer, a stirring device and a reflux condenser, 67.4 g (220 mmol) of 8-glycidyloxyoctyltrimethoxysilane ("KBM-4803" manufactured by Shin-Etsu Chemical Co., Ltd.) and 11.6 g of methanol were added and stirred evenly. A solution prepared by dissolving 0.010 g (0.11 mmol) of magnesium chloride as a catalyst in a mixture of 11.9 g (660 mmol) of water and 4.7 g of methanol was added dropwise to the mixture over 5 minutes and stirred until it became uniform. Thereafter, the temperature was raised to 70°C and a polycondensation reaction was carried out for 6 hours while stirring. After the reaction was completed, methanol and water were removed by a rotary evaporator to obtain a polyorganosiloxane compound B.

[0186] The residual rate of epoxy groups of the polyorganosiloxane compound 2 was 95% or more, the weight average molecular weight in terms of polystyrene was 4500, T3 / T2 was 2.1, and the residual amount of magnesium chloride (neutral salt catalyst) was 191 ppm.

[0187] [Hard coating composition]

[0188] <Hard Coating Composition 1>

[0189] In 100 parts by weight of the polyorganosiloxane compound A, 81.8 parts by weight of propylene glycol monomethyl ether, 0.2 parts by weight of a propylene carbonate solution of a triarylsulfonium·SbF6 salt (“CPI-101A” manufactured by San-Apro Ltd.) as a photocationic polymerization initiator, and 0.5 parts by weight of a xylene / isobutyl alcohol solution of a polyether-modified polydimethylsiloxane (“BYK-300” manufactured by BYK) as a leveling agent were mixed to obtain a hard coating composition 1.

[0190] <Hard Coat Composition 2>

[0191] A hard coat composition 2 was obtained in the same manner as in the preparation of the hard coat resin composition 1 except that the amount of the photocationic polymerization initiator was changed to 2 parts by weight.

[0192] <Hard Coating Composition 3>

[0193] A hard coat composition 3 was obtained in the same manner as in the preparation of the hard coat resin composition 1 except that the leveling agent was changed to a fluorine-based leveling agent ("MEGAFACE RS-90" manufactured by DIC) and the added amount was changed to 0.3 parts by weight based on the solid content.

[0194] <Hard Coating Composition 4>

[0195] In 100 parts by weight of the polyorganosiloxane compound B, triarylsulfonium P(Rf) was added. n F 6-n A 50% propylene carbonate solution of a salt ("CPI-200K" manufactured by San-Apro Ltd.) was added as a solid content of 0.5 parts by weight, and a leveling agent ("BYK-300" manufactured by BYK) was added as a solid content of 0.5 parts by weight to obtain a hard coating composition 4.

[0196] <Hard Coating Composition 5>

[0197] A hard coating composition 5 was obtained by adding 100 parts by weight of dipentaerythritol hexaacrylate, 25 parts by weight of propylene glycol monomethyl ether, 3 parts by weight of 1-hydroxycyclohexyl phenyl ketone ("Irgacure 184" manufactured by BASF) as a photoradical polymerization initiator, and 0.5 parts by weight of a leveling agent ("BYK-300" manufactured by BYK) as a solid content.

[0198] <Evaluation of Hard Coat Composition>

[0199] A support film having a 10 μm thick acrylic adhesive layer attached to a 125 μm thick polyethylene terephthalate film was bonded to one surface of a polyimide film 1, and a hard coating composition was applied to the other surface using a bar coater so that the dry film thickness was 50 μm. The film was heated at 120° C. for 2 minutes and then heated at an ambient temperature of 80° C. at a cumulative light intensity of about 2000 mJ / cm 2 After heating at 120° C. for 2 minutes to completely cure the hard coating composition, the film was immersed in dichloromethane to dissolve the polyimide film 1 and separate the hard coating layer (cured product of the hard coating composition).

[0200] The separated hard coating layer was used as a sample to measure the linear expansion coefficient and curing shrinkage. The linear expansion coefficient was calculated from the TMA curve when cooling from 100°C to 30°C, similarly to the transparent resin film. The curing shrinkage was calculated based on the density ρ of the hard coating composition before curing. L and the density of the hard coating after light curing ρ C , calculated based on the following formula.

[0201] Curing shrinkage (%) = 100 × (ρ C -ρ L ) / ρ C

[0202] For the hard coating compositions 1 to 3, the density ρ of the hard coating composition (solid) separated after heat drying and before ultraviolet irradiation (before curing) was measured by the density gradient tube method. L The hard coating compositions 4 and 5 were heated at 120° C. for 2 minutes to remove the volatile components (liquid) and the density ρ was measured by a pycnometer method. L The density of the hard coating after light curing is C Determined by the density gradient tube method.

[0203] The compositions, linear expansion coefficients, and cure shrinkage ratios of the hard coating compositions 1 to 5 are shown in Table 2. The compositions in Table 2 are expressed in parts by weight based on 100 parts by weight of the curable resin component.

[0204] [Table 2]

[0205]

[0206] Acrylic hard coating composition 5 showed a positive cure shrinkage. Hard coating composition 4, which used a polyorganosiloxane compound having a non-alicyclic epoxy group as a curable resin component, also showed a positive cure shrinkage. On the other hand, hard coating compositions 1 to 3, which used a polyorganosiloxane compound having an alicyclic epoxy group as a curable resin component, increased in volume (expanded) due to photocuring and showed a negative cure shrinkage.

[0207] [Hard Coat]

[0208] <Hard Coat 1>

[0209] A support film having a 10 μm thick acrylic adhesive layer attached to a 125 μm thick polyethylene terephthalate film was bonded to one surface of a polyimide film 1. The hard coating composition 1 was applied to the other surface of the polyimide film using a bar coater so that the dry film thickness was 50 μm, and heated at 120°C for 2 minutes. Thereafter, a conveyor-type ultraviolet irradiation device having an ultraviolet irradiation lamp ("Hバルブ" manufactured by Heraeus, with an output adjusted luminous intensity of 216 W / cm2) arranged at a distance of 93 mm from the coating film was used, and conveying was performed at an ambient temperature of 80°C and a conveying speed of 2 m / min, so that the accumulated light intensity measured by the UV Scale of FUJIFILM Corporation was 1950 mJ / cm2. 2 The hard coating composition was cured by irradiating ultraviolet rays in a manner of 1 to obtain a hard coating film 1 having a hard coating layer with a thickness of 50 μm on the polyimide film 1 .

[0210] <Hard Coat 2 to 10>

[0211] A hard coating film having a hard coating layer formed of a cured product of the hard coating composition 1 on the polyimide film 1 was prepared in the same manner as in the preparation of the hard coating film 1 except that the thickness of the hard coating layer and the curing conditions (the atmospheric temperature during ultraviolet irradiation and the distance between the ultraviolet irradiation lamp and the coating film) were changed. Hard coating films 4, 8, and 10 were heated at 120° C. for 2 minutes after being irradiated with ultraviolet rays.

[0212] <Hard coating films 11 to 13>

[0213] After the hard coating composition 1 was applied and heated using the polyimide film 2 instead of the polyimide film 1, a conveyor-type ultraviolet irradiation device equipped with an ultraviolet irradiation lamp (a high-pressure mercury lamp "H03-L31" manufactured by EYE GRAPHICS CO., LTD., with an output adjusted to emit light of 120 W / cm2) was used at a conveying speed of 4 m / min to achieve a total cumulative light amount from UVA to UVC of 1037 mJ / cm2 as measured by "UV POWR PUCK II" of EIT Corporation. 2 In addition, as shown in Table 4, except for changing the thickness of the hard coating layer and the atmosphere temperature during ultraviolet irradiation, a hard coating film having a hard coating layer formed of a cured product of the hard coating composition 1 on the polyimide film 2 was prepared in the same manner as the preparation of the hard coating film 1.

[0214] <Hard coating films 14 to 16>

[0215] A hard coating film having a hard coating layer formed of a cured product of the hard coating composition 1 on the polyimide film 3 was prepared in the same manner as in the preparation of the hard coating films 11 to 13 except that the polyimide film 3 was used instead of the polyimide film 2 and the atmosphere temperature during the ultraviolet irradiation was changed as shown in Table 4.

[0216] <Hard coatings 17 to 21>

[0217] A hard coating layer was applied and irradiated with light using a polyethylene terephthalate film 1 instead of the polyimide film 1 without laminating a support film. A hard coating layer having a hard coating layer formed of a cured product of the hard coating composition 1 on the polyethylene terephthalate film 1 was prepared in the same manner as in the preparation of the hard coating film 1 except that the thickness of the hard coating layer and the curing conditions (the ambient temperature during ultraviolet irradiation and the distance between the ultraviolet irradiation lamp and the coating film) were changed.

[0218] <Hard coating 22 to 36>

[0219] Hard coat films were prepared in the same manner as in the above examples except that the type of transparent resin film, the composition and thickness of the hard coat layer, and the curing conditions were changed as shown in Tables 5 and 6.

[0220] [evaluate]

[0221] The hard coating film was evaluated as follows.

[0222] <curl>

[0223] The hard coating film was cut into a 100 mm × 100 mm square, and after standing for 10 days in an environment of 23°C and 55% RH, it was placed on a horizontal table with the hard coating forming surface as the upper side, and the distance (floating amount) of the four vertices of the square from the table was measured, and the average value was taken as the curling amount. For the hard coating film that curls with the hard coating forming surface as the outer side, the curling is measured by placing it on a horizontal table with the hard coating forming surface as the lower side, and the sign of the curling amount is set to negative. For the film that cannot measure the curling value because the square film is rolled into a tube, the curling amount of the film that curls with the hard coating forming surface as the inner side is recorded as +∞, and the curling amount of the film that curls with the hard coating forming surface as the outer side is recorded as -∞.

[0224] <Surface Hardness>

[0225] The pencil hardness of the hard coating layer-formed surface was measured in accordance with JIS K5600-5-4:1999.

[0226] <Softness>

[0227] Hard coating films 1 to 16 were subjected to a cylindrical mandrel test using a type 1 tester with the hard coating layer formed on the inner side in accordance with JIS K5600-5-1: 1999. Hard coating films 1 to 16 did not crack or peel when bent along a mandrel having a diameter of 2 mm.

[0228] The materials, production conditions, and evaluation results of the hard coating films 1 to 36 are shown in Tables 3 to 6.

[0229] [Table 3]

[0230]

[0231] [Table 4]

[0232]

[0233] [Table 5]

[0234]

[0235] [Table 6]

[0236]

[0237] As shown in Table 6, the hard coating films 31 to 36 using the acrylic hard coating composition 5 having a positive curing shrinkage ratio were cut out of a square sample and rolled into a tube with the hard coating layer inside, regardless of the type of transparent resin film and the curing temperature. The hard coating film 30 using the hard coating composition 4 having a polyorganosiloxane compound having an epoxy group that is not alicyclic as a curing resin component was also rolled into a tube with the hard coating layer inside.

[0238] The hard coating films 1 to 29 using the hard coating composition having a negative cure shrinkage ratio all curled less than the hard coating films 30 to 36 .

[0239] Comparing hard coats 1 to 3, it was observed that the lower the temperature during ultraviolet irradiation, the more curling tended to occur on the negative side (the hard coat layer forming surface was the outer side). The same tendency was also observed by comparing hard coats 5 to 7 and hard coats 8 and 10. From these results, it can be seen that by using a hard coat composition having a negative curing shrinkage rate and adjusting the heating temperature during ultraviolet irradiation, a hard coat with less curling can be obtained even when the thickness of the hard coat layer is large.

[0240] The results shown in Tables 4 to 6 show that even when the type of transparent resin film, the amount of photocationic polymerization initiator in the hard coating composition, the type of leveling agent, etc. are changed, a hard coating film with less curling can be obtained by adjusting the temperature during ultraviolet irradiation. When a polyimide film is used as the transparent resin film, a tendency for the surface hardness to be higher is observed compared to when a PET film is used.

Claims

1. A hard coating film comprising a hard coating layer on a first main surface of a transparent resin film having a first main surface and a second main surface, wherein the hard coating layer is formed of a cured product of a hard coating composition, wherein the hard coating composition contains a polyorganosiloxane compound having an alicyclic epoxy group, The polyorganosiloxane compound is a condensate of a silane compound, and the silane compound includes a compound represented by the general formula (1), wherein the polyorganosiloxane compound produced by hydrolysis and condensation of the silane compound represented by the general formula (1) has a ratio T3 / T2 of a structural unit represented by the general formula (3), i.e., a T3 body, to a structural unit represented by the general formula (4), i.e., a T2 body, of 0.8 to 4, E-B-R 1 -Si(OR 3 ) x R 2 3-x …(1) [E-B-R 1 -SiO 3 / 2 ]…(3) [E-B-R 1 -SiO 2 / 2 -D]…(4) In the general formulas (1), (3) and (4), E is an alicyclic epoxy group, B is a direct bond, an ether or an ester, and R 1 is an alkylene group having 2 to 12 carbon atoms, R 2 is a hydrogen atom, or a monovalent hydrocarbon group selected from the group consisting of an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is 2 or 3, R 3 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, D is a hydrogen atom or a group selected from the group consisting of an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, The hard coating layer is formed by irradiating the hard coating composition with active energy rays at 45° C. to 85° C., The thickness of the hard coating layer is at least 0.15 times the thickness of the transparent resin film. The linear expansion coefficient of the hard coating layer is greater than the linear expansion coefficient of the transparent resin film, The hard coating composition has a negative curing shrinkage, The absolute value of the curling amount of the hard coating film measured by cutting out a square having a size of 100 mm×100 mm is 20 mm or less.

2. The hard coating film according to claim 1, wherein The polyorganosiloxane compound comprises a structure represented by general formula (5), The ratio of the number of structures represented by the general formula (5) to the total number of Si atoms in the polyorganosiloxane compound is 33% or more, [EBR 1 -Si]…(5) In the general formula (5), E is an alicyclic epoxy group, B is a direct bond, an ether or an ester, and R 1 It is an alkylene group having 2 to 12 carbon atoms.

3. The hard coating film according to claim 1 or 2, wherein: The weight average molecular weight of the polyorganosiloxane compound is 500 to 20,000.

4. The hard coating film according to claim 1 or 2, wherein: The difference between the linear expansion coefficient of the hard coating layer and the linear expansion coefficient of the transparent resin film is 5 to 100 ppm / °C.

5. The hard coating film according to claim 1 or 2, wherein: The difference between the linear expansion coefficient of the hard coating layer and the linear expansion coefficient of the transparent resin film is 30 to 50 ppm / °C.

6. The hard coating film according to claim 1 or 2, wherein: The transparent resin film includes one or more resin materials selected from the group consisting of polyester, polycarbonate, polyamide, polyimide, cyclic polyolefin, acrylic resin, and cellulose resin.

7. The hard coating film according to claim 1 or 2, wherein: The transparent resin film is a transparent polyimide film.

8. The hard coating film according to claim 1 or 2, wherein: The thickness of the transparent resin film is 10 to 150 μm.

9. The hard coating film according to claim 1 or 2, wherein: The hard coating layer has a thickness of 2 to 150 μm.

10. The hard coating film according to claim 1 or 2, wherein: The hard coating layer has a thickness of 20 to 70 μm.

11. The hard coating film according to claim 1 or 2, wherein: The thickness of the hard coating layer is 0.40 to 2.00 times the thickness of the transparent resin film.

12. The hard coating film according to claim 1 or 2, wherein: The curing shrinkage of the hard coating layer is -10 to -0.1%.

13. The hard coating film according to claim 1 or 2, wherein: The curing shrinkage of the hard coating layer is -3 to -1%. 14 . The hard coating film according to claim 1 , wherein the absolute value of the curling amount measured by cutting out a square having a size of 100 mm×100 mm is 5 mm or less. 15 . A display device comprising the hard coat film according to claim 1 on a surface of an image display panel.

16. A method for producing a hard coating film, wherein the hard coating film comprises a hard coating layer on the first main surface of a transparent resin film having a first main surface and a second main surface, the hard coating layer being formed from a cured product of a hard coating composition and having a thickness of 0.15 times or more of the transparent resin film, wherein the absolute value of the curling amount of the hard coating film measured by cutting out a square of 100 mm×100 mm is 20 mm or less, In the manufacturing method, The hard coating layer is formed by coating a hard coating composition on the first main surface of the transparent resin film and then irradiating the first main surface with active energy rays. The hard coating composition has a negative curing shrinkage, the linear expansion coefficient of the hard coating layer is greater than the linear expansion coefficient of the transparent resin film, The irradiation with active energy rays is performed in a heating atmosphere at a temperature of 45°C to 85°C.

17. The method for producing a hard coating film according to claim 16, wherein: The temperature during the active energy ray irradiation is 60°C to 85°C.

18. The method for producing a hard coating film according to claim 16 or 17, wherein: The hard coating composition comprises a condensate of a silane compound represented by the general formula (1): E-B-R 1 -Si(OR 3 ) x R 2 3-x …(1) In the general formula (1), E is an alicyclic epoxy group, B is a direct bond, an ether or an ester, and R 1 is an alkylene group having 2 to 12 carbon atoms, R 2 is a hydrogen atom, or a monovalent hydrocarbon group selected from the group consisting of an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is 2 or 3, R 3 It is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.

19. The method for producing a hard coating film according to claim 16 or 17, wherein: The hard coating composition contains a photocationic polymerization initiator.

20. The method for producing a hard coating film according to claim 16 or 17, wherein: The irradiation with the active energy rays is performed in a state where a support film having a thickness greater than that of the transparent resin film is bonded to the second main surface of the transparent resin film.

21. The method for producing a hard coating film according to claim 20, wherein: The thickness of the supporting film is 80-500 μm.

22. The method for producing a hard coating film according to claim 20, wherein: The support film can be peeled off from the transparent resin film.

23. The method for producing a hard coating film according to claim 16 or 17, wherein: After the irradiation with the active energy rays, heating is further performed.

24. The method for producing a hard coating film according to claim 23, wherein: The heating temperature of the heating after the irradiation with the active energy ray is 50 to 150°C.

25. The method for producing a hard coating film according to claim 23, wherein: The heating time of the heating after the irradiation with the active energy ray is 10 seconds to 60 minutes.

Citation Information

Patent Citations

  • Hard coat film and image display device

    JP2015069197A

  • Hard coat film suppressed in curling and method for producing same

    CN110621494A